Optical spectrum and excitons in bulk and monolayer MX2 (M=Zr, Hf; X=S, Se). Issue 4 (4th December 2015) - Abdulsalam, Mahmud; Joubert, Daniel P.
Abstract: Abstractauthoren We present first principles calculations of the electronic and optical properties of bulk and monolayer structures for four transition metal chalcogenides, MX 2   ( M = Zr and Hf; X = S, Se), using a post density functional many‐body perturbation GW approximation in conjunction with the Bethe–Selpeter approximation (GW‐BSE). Optical absorption spectra predict the presence of a strongly bound exciton that lies below the direct band gap in two bulk (HfS 2 and ZrSe 2 ) and in all the monolayer structures. The binding energy of the excitons are predicted to lie between 0.11 and 0.96 eV.